Bronchoalveolar lavage fluid cytology and airway hyper‐reactivity in clinically normal horses. Issue 8 (26th July 2018) - Cullimore, AM; Secombe, CJ; Lester, GD; Robertson, ID
Abstract : Objective: To characterise the relationship between bronchoalveolar lavage fluid (BALF) cytology and pulmonary function testing with histamine bronchoprovocation (HBP) methods in a population of clinically normal horses. Design: Cross‐sectional study Methods: Clinically normal adult horses (n = 33) underwent pulmonary function testing and HBP with a commercial flowmetric plethysmography system. BAL was performed 1–5 days later. Statistical analysis was used to assess associations between BALF cell concentration, relative inflammatory cell percentages and categorisation, and airway hyper‐reactivity (AHR). Results: AHR (PC35 ≤ 8 mg/mL) was demonstrated in 17 (52%) of the horses. Using current definitions, BALF cytology was consistent with inflammatory airway disease in 14 (42%) of the horses and 7 of those demonstrated either mastocytic and/or eosinophilic responses. There was no correlation between total inflammatory cell counts or relative percentage and AHR. No statistical association was found between BALF inflammatory cell categories and AHR. Conclusion: A direct association between cytological evidence of airway inflammation and AHR was not identified in this population of clinically normal horses. Determining the presence and measuring inflammatory cell mediators in BALF may more accurately reflect AHR. In addition, normal values for cell proportions in BALF may vary between different populations of horses and more appropriate regional reference ranges should be established.